Building collaboration through action research: the case of Ottotomo Forest Reserve in Cameroon - Jum, C.N.; Oyono, P.R. (2005)
The Ottotomo Forest Reserve in the Central Province of Cameroon is one of the protected areas in the country where several management strategies have been tested with varying degrees of success (e.g., the Tropical Shelterwood System (TSS) silvicultural technique was piloted in this forest more than 30 years ago). From 1994 with the enactment of the new forestry legislation in Cameroon, the management strategy shifted considerably, moving away from the classical ‘fences and fines’ to a collaborative approach whereby the aspirations of the local communities are taken into consideration. This paper attempts to provide an account of a collaborative management efforts facilitated by CIFOR in the reserve. Using a series of Participatory Action Research (PAR) tools, this paper identifies specific management problems, attempts to analyse those problems and establishes collaborative arrangements for future management inputs into the reserve. The paper ends with a series of lessons learned from this exercise.